Taxonomic and biotechnological potential assessment of microbial diversity on photovoltaic panels surfaces in a tropical environment - Moura, Juliane Brittez de (2021)
Photovoltaic panels can be colonized by a highly diverse microbial diversity, despite life threatening conditions. Although they are distributed worldwide, the microorganisms living on their surfaces have never been profiled or bioprospecting in tropical regions from an ecological point of view. In this work, photovoltaic panels from two cities in southeast Brazil, Sorocaba and Itatiba, were investigated using culture-independent, culture-dependent techniques and literature review to search for preliminary evidences of the colonization process and biotecnological potential. Results showed that, despite significant differences in microbial diversity (p < 0.001), the taxonomic profile was very similar for both photovoltaic panels, dominated mainly by Proteobacteria, Bacteroidota and lower amounts of Cyanobacteria phyla. A predominance of Hymenobacter and Methylobacterium Methylorubrum was observed at the genus level. Moreover, we identified a common core composed by Hymenobacter, Deinococcus, Sphingomonas, Methylobacterium Methylorubrum, Craurococcus-Caldovatus, Massilia and Noviherbaspirillum sharing genera. Predicted metabolisms focused on specific genes associated to radiation and desiccation resistance, and pigments, were detected in members of the common core and the most abundant genera. The photovoltaic panels surfaces displayed cultivable and pigmented colonies growing in a wide range of temperatures. We identified the isolated strains as Arthrobacter koreensis, Dermacoccus nishinomiyaensis, Gordonia sp., Kocuria sp., Microbacterium hydrotermale, Mycolicibacterium aurum, Verrucosispora qiuiae, Pseudomonas coleopterorum, Psychrobacter sp., Serratia nematodiphila, Sphingomonas paucimobilis, Hymenobacter flocculans, Rhodotorula mucilaginosa, Rhodotorula sp. In the literature documentation, most of these strains, or at least their closest relatives, were described as tolerant or resistant to UV light, desiccative conditions and biofilm capability, all being important adaptation mechanisms to thrive and engage the colonization process on photovoltaic panels surfaces. Moreover, a wide range of biotechnological applications was discussed, reinforcing the finding that photovoltaic panels are a repository of biotechnological interest.